Designing of a Novel Aerolysin-based Multiepitope Vaccine against Aeromonas hydrophila Isolated from Osphronemus goramy Using Reverse Vaccinology: an in Silico Approaches - Rozi; Tyasningsih, Wiwiek; Rahmahani, Jola; Aksono, Eduardus Bimo; Yunus , Muchammad; Al-Arif, Mohammad Anam; Kuncorojati, Suryo; Kusdarwati, Rahayu; Sari, Putri Desi Wulan; Amal, Mohammad Noor Azmai; Salleh, Annas; Khanand, Nadeem; Suwarno (Faculty of Fisheries and Marine Universitas Airlangga, 2024)
Graphical Abstract Highlight Research The study aims to develop a multi-epitope vaccine (MEV) against A. hydrophila by targeting the aerolysin toxin, a key virulence factor responsible for infections in fish and humans. Computational methods identified and optimized B-cell and T-cell epitopes, focusing on their ability to trigger immune responses without causing toxicity or allergenicity. In silico simulations demonstrated that the MEV has a strong binding affinity to immune receptors like TLR-4, MHC-I, and MHC-II, indicating its potential to induce robust cellular and humoral immunity. Structural analysis of the MEV showed a stable 3D conformation, with most residues in favorable regions, ensuring stability during immune activation. The MEV could enhance disease control in aquaculture and reduce human infection risks, offering a promising solution to address antibiotic resistance and the absence of effective vaccines. Abstract Aeromonas hydrophila, gram-negative, is a major pathogen responsible for various diseases in mammals, reptiles, amphibia, and vertebrates, including fish and humans. Targeting the specific toxin aerolysin in A. hydrophila is crucial to address antibiotic resistance and the lack of adequate and protective vaccines against this intracellular pathogen. This study aimed to identify a multi-epitope vaccination (MEV) candidate targeting A. hydrophila aerolysin toxin to combat the disease effectively. Standard biochemical characterization methods and sequencing of the 16S rRNA, rpoB, and aerA genes identified the isolate AHSA1 as A. hydrophila. Subsequently, we identified B and T cell epitopes on the aerolysin protein and separately predicted MHC-I and MHC-II epitopes. The epitopes are then evaluated for toxicity, antigenicity, allergenicity, and solubility. The vaccine design integrated multi-epitope-based constructs, utilizing specialized linkers (GPGPG) and EAAAK linkers to connect epitope peptides with adjuvants in the cholera toxin B component, thereby enhancing immunogenicity. Ramachandran plots showed that 85.25% of the residues were located in the most favorable regions, which was followed by the generously allowed zone (1.30%), the additional allowed regions (10.80%), and the forbidden regions (2.65%), thus confirming the feasibility of the modeled vaccine design. Based on docking simulations, MEV had the highest binding and interaction energies with TLR-4, TLR-9, MHC-I, and MHC-II (-1081.4, -723.2, 866.2, -9043.3 kcal/mol). Based on computational modelling, we expect the Aerolysin MEV candidate design to activate diverse immune mechanisms, stimulate robust responses against A. hydrophila, and maintain safety. The significant solubility, absence of toxicity or allergic response, and minimal side effects in animal testing all contribute to the potential clinical utility of this vaccine candidate.